Hi Debbie. Remember that a square has all sides the same length. That means its side length is one quarter its perimeter. We'll be using that.
Let's use some variable names:
P = the perimeter of the new square
p = the perimeter of the original square
S = the side length of the new square
s = the side length of the original square
You are told that
S = s + 2
and
P + 3 = 5s
and you want to find "s". So using the relationship between a square's side length and its perimeter (4S = P) we can see that we first substitute 4S for P in
P + 3 = 5s
and get
4S + 3 = 5s
Now we substitute S = s + 2 into that to get
4(s+2) + 3 = 5s
Now rearrange to solve for s.
Stephen La Rocque>
